Outcome of Hypospadias Repair: 4 Years Experience in King Abdulaziz University Hospital: A Retrospective Study - Osam M. Rayes, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Hypospadias is one of the most frequently seen urogenital disorder all over the world. The study of all records of seventy patients operated for hypospadias repair in King Abdulaziz University Hospital (KAUH), Jeddah, Saudi Arabia were reviewed by the author and/or his team from June 2005 to May 2009. More than half of them were operated upon the age of 2 years (57%) and under. The native meatus was distal penile, mid-penile and proximal penile in 53, 9 and 8 patients, respectively. Nearly half of the patients were repaired using the TIP "Snodgrass" technique and meatalbased flap "Mathieu" technique was the next common used. In this work, a four years' experience in treating hypospadias cases ranging from glanular to scrotal level of severity using several techniques was evaluated. Results and conclusions are presented.